2020
DOI: 10.1177/2041669519899108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Optical Flow Motion Direction on Vection Strength

Abstract: In some phenomena of visual perception, the motion direction of visual stimuli can affect perception. In particular, asymmetries between oblique directions and cardinal (horizontal and vertical) directions have been reported and are known as oblique effects (e.g., contrast sensitivity and motion threshold). In this study, we investigated how vection strength depends on motion direction. Participants observed random-dot optical flow in a circular field and rated the perceived vection strength. Dot movement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Any deficits in processing optic flow information should distort self-motion perception. Studies have found that vection strength is influenced by changes in the pattern of retinal motion 12 14 . It was found that reducing retinal adaptation to visual motion, such as by oscillating around a fixation point, appeared to help sustain the sensitivity to retinal motion stimulation caused by optic flow, which generated stronger overall vection 12 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any deficits in processing optic flow information should distort self-motion perception. Studies have found that vection strength is influenced by changes in the pattern of retinal motion 12 14 . It was found that reducing retinal adaptation to visual motion, such as by oscillating around a fixation point, appeared to help sustain the sensitivity to retinal motion stimulation caused by optic flow, which generated stronger overall vection 12 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that vection strength is influenced by changes in the pattern of retinal motion 12 14 . It was found that reducing retinal adaptation to visual motion, such as by oscillating around a fixation point, appeared to help sustain the sensitivity to retinal motion stimulation caused by optic flow, which generated stronger overall vection 12 14 . Eye-movements also affect retinal motion and displacement of the focus of expansion, which in turn, can enhance the overall strength of vection 15 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this is a plausible idea, as human visual motion perception is primarily based on the optical flow, as first discovered by Gibson [21] and further confirmed in brain science research [22], [23]. In follow-up studies, methods have been devised to modulate the degree or characteristics of vection by manipulating the optical flow form [24], overlapping different directional/rotation flows [25], and mixing in visual noise [26]. In fact, the human brain can differentiate between the visual motion caused by oneself and those caused by objects in the visual field, particularly when facilitated by the vestibular sense [27].…”
Section: Mcgill Et Al Investigated the Effects Of Visual Motion Cues ...mentioning
confidence: 92%
“…In both the abstract and the naturalistic condition, a focus marker was used. Focus markers are commonly used in vection research (e.g., [40], [41]) and was included in our study for the comparison between conditions with and without a secondary task (see [34] for results).…”
Section: Designmentioning
confidence: 99%